Bank Asset Quality in Emerging Markets : Determinants and Spillovers - De Bock, Reinout (IMF Working Papers; Working Paper, 2012)
This paper assesses the vulnerability of emerging markets and their banks to aggregate shocks. We find significant links between banks' asset quality, credit and macroeconomic aggregates. Lower economic growth, an exchange rate depreciation, weaker terms of trade and a fall in debt-creating capital inflows reduce credit growth while loan quality deteriorates. Particularly noteworthy is the sharp deterioration of balance sheets following a reversal of portfolio inflows. We also find evidence of feedback effects from the financial sector on the wider economy. GDP growth falls after shocks that drive non-performing loans higher or generate a contraction in credit. This analysis was used in chapter 1 of the Global Financial Stability Report (September 2011) to help evaluate the sensitivity of banks' capital adequacy ratios to macroeconomic and funding cost shocks.